2005
DOI: 10.1103/physreve.71.066313
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency in two-dimensional turbulence with drag

Abstract: We consider the enstrophy cascade in forced two-dimensional turbulence with a linear drag force. In the presence of linear drag, the energy wavenumber spectrum drops with a power law faster than in the case without drag, and the vorticity field becomes intermittent, as shown by the anomalous scaling of the vorticity structure functions. Using previous theory, we compare numerical simulation results with predictions for the power law exponent of the energy wavenumber spectrum and the scaling exponents of the vo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 38 publications
5
44
0
Order By: Relevance
“…However, this is far from conclusive as the viscousconvective ranges accessible to modern computers are still quite limited. Furthermore, a number of studies [16,[24][25][26] have either argued for or found spectra shallower than the Batchelor spectrum. For these reasons, as well as the phenomenological nature of the Obukhov-Corrsin and Batchelor theories, further theoretical consideration and numerical analysis (with higher resolutions whenever possible) continue to be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is far from conclusive as the viscousconvective ranges accessible to modern computers are still quite limited. Furthermore, a number of studies [16,[24][25][26] have either argued for or found spectra shallower than the Batchelor spectrum. For these reasons, as well as the phenomenological nature of the Obukhov-Corrsin and Batchelor theories, further theoretical consideration and numerical analysis (with higher resolutions whenever possible) continue to be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Direct numerical simulations (DNS) of freely-decaying 2D FDT (McWilliams [22], Benzi et al [23], Brachet et al [24] and [25], Kida [26], Ohkitani [27], Schneider and Farge [28]) and forced-dissipative 2D FDT (Basdevant et al [29], Legras et al [30] and Tsang et al [31]) showed intermittency caused by the presence of coherent structures. These structures inhibit the local inertial transfer of enstrophy via phase correlations across many length scales and produce energy spectra which are steeper than the Kraichnan-Batchelor spectrum E(k) ∼ k −3 for the enstrophy cascade.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to coherent structures, another cause of intermittency in the 2D enstrophy cascade can be contamination from the 3D effects in any real flow situation. In the geophysical context, it can be caused by the Ekman drag ( [31]) which simulates the frictional planetary boundary layer (Pedlosky [33]). The Ekman drag acts also as a sink at low wave numbers to take out the 'condensate' from the inverse energy cascade.…”
Section: Introductionmentioning
confidence: 99%
“…In two dimensions, the effects of linear damping which is active in all scales (as opposed to Rayleigh friction which is active only at the largest scales) has been studied in recent years (Boffetta et al 2002;Tsang et al 2005;Tsang & Young 2009). It should be noted that both linear forcing and linear damping are active over all scales, including the energy and enstrophy inertial ranges.…”
Section: Introductionmentioning
confidence: 99%